1981
DOI: 10.1046/j.1537-2995.1981.21381201811.x
|View full text |Cite
|
Sign up to set email alerts
|

The Elimination of Hydroxyethyl Starch from the Blood of Donors Experiencing Single or Multiple Intermittent‐Flow Centrifugation Leukapheresis

Abstract: The elimination of hydroxyethyl starch (HES) from donor blood was studied following either single or multiple intermittent‐flow centrifugation leukapheresis. Immediately following pheresis, serum HES concentrations fell rapidly. The rate of elimination then slowed with trace amounts of HES persisting for weeks. Pharmaco‐kinetic analysis using a two‐compartment open model revealed an average distribution half‐life and terminal half‐life of 3.84 and 48 days, respectively. After multiple phereses, HES accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…Only when donors received HES were T-cell func tions lowered or impaired. The mechanism or cause of the HES effect is unknown [9].…”
Section: Discussionmentioning
confidence: 99%
“…Only when donors received HES were T-cell func tions lowered or impaired. The mechanism or cause of the HES effect is unknown [9].…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone was given orally either as a single dose (50 mg) about 12 h before leukapheresis, or in three divid ed doses (20 mg each) 15, 12 and 2 h before the procedure. suits in serious side-effects, temporary ab normalities in some blood chemistries [12,13], coagulation parameters [23], and plasma volume expansion after multiple transfu sions have been reported [12]. Recent studies have shown that a fraction of the infused HES is eliminated very slowly within the course of 1 year [13,14], generating uncer tainty about the safety of administering HES to leukapheresis donors repetitively.…”
Section: Resultsmentioning
confidence: 99%
“…The average increase of serum polysac charide concentration following the low HES leukapheresis procedure was about 100 mg/dl, which is about 20% of the values reported after the standard leukapheresis procedure [12][13][14], It should be noted that although the donor received a low dose of HES, the amount of HES added to the RBC during the separation was not less than that given during the standard leukapheresis pro cedure. Even multiple procedures resulted in a lower exposure of the donor to HES than one standard leukapheresis procedure, as is shown in a case where three procedures were performed in the course of 8 days ( fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously reported a low-dose HES leukapheresis technique with good granulocyte yields [1] in which the amount of HES given to the donor is about 20% of that administered during standard discontin uous-flow leukapheresis [2,3].…”
Section: Introductionmentioning
confidence: 99%